Factors Influencing Adaptation Of Indigenous Students At Selected Public Universities In Malaysia - Doreen, Primus (2019)
Despite an increase in access to tertiary education, poor performance and high dropouts among the indigenous students are still evident. Past studies from Australia, Canada and New Zealand show that indigenous students’ failure to adapt to academic and social life in the campus was a contributing factor. However, study on indigenous students in the local university context is still scarce, hence, not much is known about their state of adaptation. To fill in the literature gaps, this study aims to determine the level of adaptation among indigenous students at public universities in Malaysia and explore whether their adaptation differs according to demographic profile. A Mixed Method Sequential Explanatory Design was carried out to achieve the objectives of the study. Data was collected through both quantitative and qualitative approaches. Quantitatively, 160 (n=160) indigenous students from 10 public universities were sampled through purposive sampling. Their adaptation was measured by the Self-Adaptation to College Questionnaire (SACQ). Instruments that were used to measure factors related to indigenous’ adaptation were self-esteem scale, resiliency scale, self-regulation scale and the support scale. Qualitatively, 12 indigenous students have participated in semi-structure interviews to explore the challenges faced by them when studying at the university and to understand the sources of the support that they received. The findings revealed that indigenous students’ have moderate level of academic adaptation (m=2.93), high level of socio-emotional adaptation (m=3.07) and high overall adaptation (m=3.02).Level of adaptation also differ according to their demographic such as first-generation, ethnicity and household income.